Influence of Na+ and Ca2+ on flame retardancy, thermal degradation, and pyrolysis behavior of cellulose fibers. (10th February 2017) - Shi, Ran; Tan, Liwen; Zong, Lu; Ji, Quan; Li, Ximei; Zhang, Keke; Cheng, Lingling; Xia, Yanzhi
Highlights: Flame-retardant cellulose–Na and cellulose–Ca fibers were successfully synthesized. Na + and Ca 2+ effectively improved the flame retardancy of cellulose fibers. TG and the DTG showed the thermal decomposition process of cellulose–Na/Ca fibers. GC–MS revealed the different pyrolysis behavior of cellulose–Na/Ca fibers. Abstract: Flame-retardant cellulose–Na and cellulose–Ca fibers were successfully synthesized by grafting Na + and Ca 2+ onto cellulose fibers, and confirmed by FTIR. The combustion behavior of the fibers was assessed by the limiting oxygen index (LOI) and cone calorimeter (CONE). The maximum LOI values of cellulose–Na and cellulose–Ca fibers were 31 and 30, which are higher than that (19) of cellulose fibers. The CONE results showed that the values of heat-release rate and total heat release for cellulose–Na and cellulose–Ca fibers were significantly lower than those for cellulose fibers. The thermogravimetric analysis (TG) and differential thermogravimetric analysis (DTG) curves in the continuous and trigger modes showed that the cellulose–Na and cellulose–Ca fibers generated more residues than cellulose fibers. Thermogravimetric analysis–gas chromatography–mass spectrometry was used to detect the characteristic gases produced in the pyrolysis of cellulose–Na and cellulose–Ca fibers.